Impact of fatigue on situation awareness of healthcare professionals - Dara, Sarita (2014)
This study explores the impact of fatigue on Situation Awareness (SA) both before and after the incorporation of a Fatigue Risk Management System (FRMS). It explores the relationship between fatigue and SA and the impact of FRMS on both fatigue and SA. Literature review showed that fatigue impacts workplace safety and health and public safety and health. In healthcare sector, the consequences of shift work induced fatigue in healthcare professionals can adversely impact patient safety. Workplace Safety and Health (Risk Management) Regulations in Singapore mandate the assessment and management of all identified risks and occupational safety and health best practices suggest performance based customised Fatigue Risk Management System (FRMS) as the best option. However healthcare sector continues to manage shift work related fatigue risk through prescriptive hours of service guidelines. Impact of fatigue on cognitive functions such as memory, attention and decision making have been extensively studied but the impact of fatigue on SA, which is an upstream indicator of cognitive presence is not clearly defined. This study was conducted in Surgical Intensive Care Unit (SICU) nurses in a tertiary care hospital in Singapore over 4 main phases: Preliminary studies, Pre FRMS, FRMS and Post FRMS. In the preliminary studies and Pre FRMS phase, fatigue and SA of nurses working in rotating shifts were analysed through roster analysis, fatigue survey, fatigue and sleepiness measures, actigraphy, vigilance testing and SA estimation. A healthcare model for FRMS was developed and implemented in SICU. FRMS included modifications to the SICU work roster to optimise the work and rest schedules, education of nurses on fatigue self-management during work as well as during the rest period, working with the SICU management for provision of alertness measures and fatigue countermeasures for the shifts identified as high risk. Measures for fatigue and SA were repeated in the Post FRMS phase. Results of Pre and Post FRMS phases were compared. The results provide an insight into the relationship between fatigue arising from shift work and SA in health care workers in a naturalistic field setting. Results showed that implementation of FRMS in SICU was associated with reduction in fatigue scores and improvements in SA scores. This study identifies the fatigue assessment tools that have the potential to be used in the healthcare sector for assessment of fatigue related to shift work. It also demonstrates the relevance and effectiveness of FRMS in nurses in SICU.